Vitamin D Supplementation for Obesity: Potential Mechanisms of Action and an Update of Randomized Controlled Trials - Soares, Mario; Pathak, K. (Bentham Science Publishers Ltd, 2014)
Background: Obesity often coexists with poor vitamin D status. There is emerging evidence that improving vitamin D status could lower prevalence of many chronic diseases. We questioned whether vitamin D influenced body fat mass. Methods: A literature search from 1995 to date was conducted using prominent databases. Selection criteria included human, randomized controlled trials (RCTs) that were designed to test the supplementation of vitamin D on body weight and composition. Results: Eleven RCTs (4 primary and 7 secondary) that supplemented vitamin D met our criteria. Nine studies were of good quality with a Jadad et al. score ≥3. Three favoured an effect of vitamin D on body fatness, while six showed no difference between treatments. Better vitamin status before or during an RCT predicted greater weight and/or fat loss in a few trials. Conclusion: Current evidence from RCTs of good quality did not unequivocally support the contention that vitamin D accelerated weight or fat loss in obesity. Direct mechanistic pathways for obesity prevention remain untested in humans, though an indirect effect through an improvement in calcium metabolism, was plausible. Outcomes from trials recently completed or in progress will strength the evidence base in this important area.